2022
DOI: 10.1177/00469580221126307
|View full text |Cite
|
Sign up to set email alerts
|

“I Felt Grounded and Clear-Headed”: Qualitative Exploration of a Mind-Body Physical Activity Intervention on Stress Among College Students During COVID-19

Abstract: The COVID-19 pandemic affected college students’ overall health. The aims of this qualitative inquiry were to provide a more comprehensive understanding of the effectiveness of the mind-body physical activity (MBPA) intervention and to explore the MBPA intervention experiences through the use of journals and photographs (photovoice) of a purposeful sample of 21 college students during the COVID-19 pandemic. An inductive qualitative process was used to explore the data that emerged from photovoice images and jo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…This finding was also highlighted by other international publications knowing that this outbreak has imposed a situation of socio-economic crisis and national restrictions that ended-up with profound psychological distress and various mental problems including stress, anxiety, depression, and frustration. 116 , 117 Similarly, changes in existing mental health may be in part explained by the imposed restrictions of the Lebanese government that provided a more structured daily routine and increased exposure to external stressors such as the major political and economic crisis. Mental health problems were observed across most population sub-groups (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…This finding was also highlighted by other international publications knowing that this outbreak has imposed a situation of socio-economic crisis and national restrictions that ended-up with profound psychological distress and various mental problems including stress, anxiety, depression, and frustration. 116 , 117 Similarly, changes in existing mental health may be in part explained by the imposed restrictions of the Lebanese government that provided a more structured daily routine and increased exposure to external stressors such as the major political and economic crisis. Mental health problems were observed across most population sub-groups (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Interventions aiming to improve weekday sleep may want to consider using methods to improve college students' mental health. Various approaches are available to improve mental health in young adults; however, incorporating stress reduction techniques and mindfulness activities into daily routines has been shown as an efficient and effective way to lower anxiety and improve mood (46)(47)(48).…”
Section: Discussionmentioning
confidence: 99%
“…Students reported that the intervention affected their well-being making them feel "more grounded and focused." They also reported a desire to "implement the intervention techniques post-study to increase well-being" and their appreciation of being part of the study which "lowered the stress of being in college during the pandemic" [27].…”
Section: What Has Been Studied So Far?mentioning
confidence: 99%